Delinquency Best Treatments: How to Divert Youths from Violence While Saving Lives and Detention Costs. (4th June 2013) - Zagar, Robert John; Grove, William M.; Busch, Kenneth G.; Felthous, Alan R.; Saß, Henning
<x xml:space="preserve">Abstract</x> Youth development and violence prevention are two sides of the same public policy. The focus of much theoretical and empirical effort is identifying delinquency risks and intervening. Given the great costs of homicide and the historically high nationwide prison population, new policies must address increasing violence and rising expenses. Treatments of prenatal care, home visitation, bullying prevention, alcohol‐substance abuse education, alternative thinking promotion, mentoring, life skills training, rewards for graduation and employment, functional family and multi‐systemic therapy, and multi‐dimensional foster care are effective, because they ameliorate age‐specific risks for delinquency. At present, these interventions only yield a 10–40% diversion from crime however. Returns on investment (ROIs) vary from $1 to $98. Targeting empirical treatments to those determined to be most at risk, based on statistical models or actuarial testing, and using electronic surveillance for non‐violent prisoners significantly diverted youth from violence, improving ROI, while simultaneously saving costs. Copyright © 2013 John Wiley & Sons, Ltd.